Switch in 3′ Splice Site Recognition between Exon Definition and Splicing Catalysis Is Important for Sex-lethal Autoregulation - Penalva, Luiz O. F. (American Society for Microbiology, 2001)
Maintenance of female sexual identity in Drosophila melanogaster involves an autoregulatory loop in which the protein Sex-lethal (SXL) promotes skipping of exon 3 from its own pre-mRNA. We have used transient transfection of Drosophila Schneider cells to analyze the role of exon 3 splice sites in regulation. Our results indicate that exon 3 repression requires competition between the 5′ splice sites of exons 2 and 3 but is independent of their relative strength. Two 3′ splice site AG's precede exon 3. We report here that, while the distal site plays a critical role in defining the exon, the proximal site is preferentially used for the actual splicing reaction, arguing for a switch in 3′ splice site recognition between exon definition and splicing catalysis. Remarkably, the presence of the two 3′ splice sites is important for the efficient regulation by SXL, suggesting that SXL interferes with molecular events occurring between initial splice site communication across the exon and the splice site pairing that leads to intron removal.